Market definition of the German retail gasoline industry on highways and those in the immediate vicinity - Kleineberg, Christoph (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
The geographical definition of markets is a crucial challenge for economists. With the availability of multiple tools to compare prices, the idea of market definition is entering a new era as it infiltrates the digital sphere. Since December 1st, 2013 the market transparency unit of the Federal German Cartel Office is forwarding all prices, for every gasoline type, at every gasoline station in Germany at all times, through consumer information services to consumers by the means of websites or smartphone apps. Gasoline is a perfectly homogenous product as there is no alternative for its consumption by car, bus or truck drivers in the short or medium run. The availability of price data allows us to study what premiums drivers are willing to pay in order to avoid search costs or additional driving distances. The research question is how prices of highway gasoline stations are dependent upon prices offered by street gasoline stations in the vicinity, and what additional price customers are willing to pay to avoid searching for another gasoline station away from the highway. Results indicate that there is a premium of 10 to 11 cents per litre throughout the day and 15 cents per litre in the evening on gasoline sold by stations on the highway. When checked for robustness, results indicate that the pricing behavior of gasoline stations differ depending on the particular market environment. There is no uniform pricing behavior of highway gasoline stations. Some highway gasoline station are setting their prices independently from the gasoline stations in the vicinity, other are acting like regular gasoline stations and do not even charge an additional premium. Furthermore, a high frequency of traffic on highways leads to lower prices whereas a high population density leads to higher prices.
Keywords: Market Definition; Applied Economic; Gasoline Market; 330 Wirtschaft